(untitled) (Damascus University Journal of educational and Psychologyical sciences, 2023)
The research aims to reveal the concepts of legal education that are available in the social studies curricula in the basic education stage (1st cycle), to achieve this aim, the descriptive analytical approach Was used, and a list of legal educational concepts was prepared. The list consists in its final form of (7) main legal fields and (39) Legal sub-concepts. Depending on this list, a content analysis form Was designed. The results of the research indicated that The availability of legal concepts in social studies books of the First cycle is insufficient, The highest percentage was 29.52% For the criminal domain and the lowest For the family domain 0% , and it moved away from the criterion of continuing to present the main and subsidiary legal education concepts .The study suggested to include the list of legal Concepts in the development plans of the content of social studies Curricula (1st cycle), and expanding the field of analytical studies of the other subjects and the other stages of education the light of the legal educational concepts.